INFLUENCE OF AGE ON PARAMETERS FOR FEMOROACETABULAR IMPINGEMENT AND HIP DYSPLASIA IN X-RAYS - Ulf-krister Hofmann (Acta Ortopédica Brasileira, 2017)
Objective: While several radiographic parameters have been established to describe the geometry and pathology of the hip, their reference values and clinical significance remain a matter of dispute. The present study tests the hypothesis that age has a relevant impact on radiographic hip parameters. Method: Pelvic antero-posterior views were measured for CE angle, Sharp´s angle, acetabular depth-to-width ratio, femoral head extrusion index, roof obliquity, caput-collum-diaphyseal (CCD) angle, and Murray´s femoral head ratio, and the values obtained were correlated with age. Results: Significant weak and moderate linear correlations (all Ps<0.001) were observed between age and CE angle ( ρ =0.31), Sharp´s angle ( ρ =-0.38), extrusion index ( ρ =-0.22), CCD angle ( ρ =-0.15), depth-to-width ratio ( ρ =-0.38), and roof obliquity ( ρ =-0.19), while Murray´s femoral head ratio ( ρ =0.05; P=0.274) was not associated with age. Interestingly, the parameters describing the acetabulum all showed a relevant increase in coverage with age, leading to CE-angles well beyond 40∞ and a Sharp´s angle below 35∞ in a large portion of asymptomatic older adults. Conclusion: While a decrease in CCD angle with age is described in most ortho- pedic textbooks, the changes observed with age in acetabular geometry far exceed those measured at the femoral head-neck junction. We recommend considering these alterations that may be attributable to age when formulating a radiographic diagnosis. Level of Evidence III, Diagnostic Studies-Investigating a Diagnostic Test.